THE CONTRACTOR SELECTION CRITERIA AFFECTING PROJECT PERFORMANCE CONSTRUCTION SEBA PIER PORT FACILITIES, SABU RAIJUA, NTT - Khakimin, Achmad Lukmanul; Witjaksana, Budi; Tjendani, Hanie Teki (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
The selection of contractors will affect the performance of the project to be implemented. The criteria for selecting a contractor consist of 3 factors, namely Factor 1 which includes accuracy, reputation, and cooperation relationships, Factor 2 which includes knowledge of work, work ability, initiative, and social ability as well as Factor 3 which includes work experience, control, and commitment. This study aims to analyze the criteria for selecting contractors that affect the performance of construction projects. This research was conducted using quantitative methods by conducting field surveys or field studies. The sample population in this study was Seba Pier Port Facilities Project, Sabu Raijua, NTT Owner as many as 57 people. The analysis technique in this study was Multiple Linear Regression Analysis. The results of the research and discussion can be concluded that The criteria for selecting a contractor that affects the performance of a construction project are price, financial capability, equipment support, and contractor performance. Meanwhile, the criteria for experience and occupational safety and health (K3) do not affect the performance of construction projects. Meanwhile, if the contractor had the appropriate benchmark price, financial capability, equipment support, and performance of the contractor, then the performance of the construction project will certainly be good.